PENGARUH LITERASI KEUANGAN DAN DIGITALISASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN UMKM - Brilliani Raras Sakapuspa; Abdul Wahab; Irna Hidayah; Wina Sari Asmara; Raden Hebat Kurnia (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of financial literacy and accounting digitalization on the quality of financial reports of Micro, Small, and Medium Enterprises (MSMEs). The quality of financial reports is a crucial aspect in business management because it forms the basis for business decision-making, performance evaluation, and access to financing sources. However, many MSMEs still face obstacles in preparing accurate and standardized financial reports. Financial literacy and accounting digitalization are seen as factors that can improve the quality of financial reports by increasing financial understanding and utilizing technology in the financial recording and reporting process. This study uses a quantitative approach with a survey method. Data were obtained by distributing questionnaires to MSMEs who served as research respondents. The sampling technique used purposive sampling with certain criteria according to the research objectives. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination (R²) to examine the influence of independent variables on the dependent variable. The results show that financial literacy has a positive and significant effect on the quality of MSME financial reports. Accounting digitalization has also been shown to have a positive and significant effect on the quality of MSME financial reports. Furthermore, financial literacy and accounting digitalization simultaneously have a positive and significant impact on the quality of MSME financial reports.